Perbedaan Derajat Aglutinasi Pemeriksaan Golongan Darah Metode Tabung Berdasarkan Konsentrasi Suspensi Sel 5% Segera Periksan Dengan Lama Penyimpanan 5 Hari - Dewi Hartati; Hanny Rizky Ananda; Denny Juraijin (jurnal kesehatan terapan sains dan teknologi, 2024)
Background: ABO b;ood group examination is an examination carried out to determinate the type of blood group in humans that detects the presence of antigens on the surface of the red blood cell membrane by means of the Tube Method various consentrations of erythrocyte cell suspension,namely 5%, 10% and 15%. Research purpose: To determinate the effect of various consentrations of erythrocyte cell suspension with ready-to-use 0,9% NaCl and 0,9% table salt solvent on the degree of agglutination in blood group examination Tube method. Research method: This research is a pure experimental study with a total sample 41 people, this study was conducted on January 16-20, 2023 at the Muhammadiyah Palembang IKesT Clinical Pathology Laboratory. Results: The results showed that the blood group examination was done by the tube method with a concentration of erythrocyte cell suspension, namely 5%, 10% and 15% with 0,9% NaCl solvent ready-to-use and 0,9% NaCl, table salt solvent resulting in a degree of agglutination of +4. The Kruskal-wallis test result in the Cell Grouping method obtained 0,000 and in the Serum Grouping method obtained 0,051. Conclusion: The conclusion in this study is that there is no effect of various consentrations of erythrocyte cell suspension with ready-to-use 0,9% NaCl and 0,9% NaCl Solvent Kitchen Salt on the degree of agglutination in blood group examination Tube Method so that 0,9% NaCl solvent from table salt can be used as an alternative to ready-to-use 0,9% NaCl reagent in blood group tests by tube method. Keywords: Blood type, Aglutination